Thermo-responsive injectable hydrogels for sustained drug delivery - Ng, Elson Weilong (Nanyang Technological University, 2023)
Hydrogels are widely used in the biomedical field due to their biocompatibility and similarity to the extracellular matrix. Most of the hydrogels used are crosslinked prior to application and are therefore implanted using surgical procedures. Injectable hydrogels are attractive as they are less invasive and do not require open wound surgical procedures. In order to make conventional hydrogels injectable, polymerization has to be done in the body instead. This has risks associated with the unreacted chemicals during in situ polymerization. On the other hand, thermogels, a type of smart hydrogel that is responsive to temperature stimuli, can be safely injected into the body with minimal risk of monomer toxicity. The unique heat-induced sol-to-gel transition allows them to be in solution below body temperature and gel at body temperature, making them an ideal candidate as an injectable hydrogel. However, the use of physical micellar crosslinks in thermogels makes them mechanically weak. Inspired by a strong protein such as collagen that uses hydrogen bonding to get its strength, we attempt to improve the mechanical properties through the incorporation of dihydroxy groups into a particular thermogel of interest. We have studied the effects of how the increase in dihydroxy concentration in the thermogel affects the storage modulus and provided insights into how this affects the functional properties. We found that as the number of hydroxy groups increases, the strength of the thermogel decreases due to the hydrophilicity. However, there is a notable improvement in the processibility at 25 °C and retention of injectability at high concentrations of 25wt% polymer concentration. The high concentrations allow sustained drug delivery due to a decrease in the thermogel mesh size and an increase in its interaction with therapeutics via hydrogen bonding.